Situational Analysis for Complex Systems: Methodological Development in Public Health Research - Wanda Martin; Bernie Pauly; Marjorie MacDonald (AIMS Press, 2016)
Public health systems have suffered infrastructure losses worldwide. Strengthening public health systems requires not only good policies and programs, but also development of new research methodologies to support public health systems renewal. Our research team considers public health systems to be complex adaptive systems and as such new methods are necessary to generate knowledge about the process of implementing public health programs and services. Within our program of research, we have employed situational analysis as a method for studying complex adaptive systems in four distinct research studies on public health program implementation. The purpose of this paper is to demonstrate the use of situational analysis as a method for studying complex systems and highlight the need for further methodological development.